Reawakening the Nation: British journalists and the interwar debate on the origins of the First World War. (18th May 2016) - Orgill, Nathan N.
Abstract : Scholarly interest in the interwar debate on the origins of the Great War has focused on the role played by historians and decision-makers, which eventually settled into a revisionist consensus stressing collective responsibility. This article reexamines the role played by British journalists in the early political debate on the origins of the war, recapturing the interpretations of journalists, editors, and political commentators after World War I. Through postwar memoirs, books centered on the origins of the war, essays, and other writings, many of the most prominent British journalists focused on making the case for German war guilt after 1914. In doing so, they mostly worked to support the official judgment of the Versailles Peace Treaty against revisionist historians and opinion in Britain and abroad. The interpretation developed by British journalists in this period thus served as a direct counterfoil to the revisionist consensus of this period and continues to resonate even up to the present day among those who see World War I as Britain's "good war."